Children with Learning Problems: A Developmental View for Parents. - Adams, Ruth R.; Lerner, Lillian; Anderson, Judith (Journal of Learning Disabilities, 1979)
Discusses the role of parents in the treatment of children's learning problems. Effect of interpersonal stress at home and school on learning; Importance of understanding the reading process in its developmental context in helping parents understand the concept of maturation gap.